Global excellence in rheumatology: Africa–The contribution of African women rheumatologists - Hmamouchi, Ihsane; Adebajo, Adewale (Frontiers in Medicine, 2022)
Over the last few decades, the development of Rheumatology on the African continent has made great strides. Alongside an increasing recognition of the prevalence and burden of disease from these conditions, has been a determination to raise awareness of these disorders in Africa together with an appreciation of the associated disease impact on individuals, families and society as a whole. Great improvements have also been made across the continent with regard to the education of medical students, trainee doctors and allied health professionals for these conditions. Furthermore, high-quality rheumatological research is now emanating from Africa. Taken together, these actions mean that Africa is making a significant contribution to global excellence in Rheumatology. Although this achievement has been made possible by visionary, hardworking and inspirational men and women, we believe that it is vital to bring to light the extraordinary efforts of African female rheumatologists in this endeavour. Their contribution is all the more remarkable because of the barriers that women still face in medicine in general and in academia in particular. We showcase here, four women of distinction who in their own unique way, have exemplified the contribution of African female rheumatologists to global excellence in Africa. We pay tribute to them and to their ongoing efforts to act as beacons of excellence in rheumatology in Africa to men and especially to other women.